Effect of Different Soil Treatments on the Quality of Soybean Flour and Milk - EC, Omah; CV, Azuka; KC, Obiorah (International Journal of Sustainable Agricultural Research, 2022)
The study investigated the influence of fertilization treatments and tillage on the quality of soybean flour and milk samples. The fertilization treatments were as follows: 10t/h (4.5kg) organic; 5t/ha (2.25kg organic + 50%NPK 15:15:15); 15t/ha (6.75kg organic + 50% NPK 15:15:15); 10t/ha (4.5kg + 50% NPK 15:15:15); 100% NPK 15:15:15 and control (no treatment). These applications were made on tilled and non- tilled soils respectively and cumulated to sample codes T1, T2, T3, T4, T5, T6, NT1, NT2, NT3, NT4, NT5 and NT6. The soybean samples were milled and the samples were subjected to functional and chemical analyses. These samples were used to produce soymilk which was subjected to sensory evaluation. The functional properties results for bulk density, swelling capacity, water absorbing capacity (WAC), foaming capacity and pH ranged from 0.54-0.69%, 87-248%, 0.65-1.45%, 5.45-31.70% and 5.90-6.40 respectively. Proximate composition of the samples ranged from 6.32-11.33% moisture, 26.45-49.65% protein, 15.09 -18.65% fat, 4.69-8.22% ash, 5.05-13.73% crude fibre and19.95-32.40% carbohydrate. The mineral composition ranged from 32.30 – 49.56 mg/100g, 0.05 – 0.07 mg/100g and 0.04 - 0.35 mg/100g for calcium, iron and potassium respectively. The vitamin content ranged from 1.19 – 2.52mg/100g, 0.18-0.39mg/100g, 0.01 - 0.03mg/100g and 9.80-13.41 mg/100 for B1, B2, B12 and B6 respectively. The anti-nutrient result for phytate, trypsin inhibitor and heamaglutinin ranged from 0.11-0.20 mg/100g, 0.05-0.13 mg/100g and 0.56-1.44 Hu/gm respectively. Samples obtained from tilled soil showed best results. Sensory results of the soymilk showed improved attributes when compared to the control samples.